2004
DOI: 10.1029/2003jc001806
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rain on air‐sea gas exchange: Lessons from a model ocean

Abstract: [1] Rain has been shown to significantly enhance the rate of air-water gas exchange in fresh water environments, and the mechanism behind this enhancement has been studied in laboratory experiments. In the ocean, the effects of rain are complicated by the potential influence of density stratification at the water surface. Since it is difficult to perform controlled rain-induced gas exchange experiments in the open ocean, an SF 6 evasion experiment was conducted in the artificial ocean at Biosphere 2. The measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 61 publications
5
82
1
1
Order By: Relevance
“…N 2 O and SF 6 were measured in 50 mL ground glass syringes via the headspace method (Ho et al, 2004). Approximately, 30 mL of ultra-high purity (UHP) nitrogen was added to each syringe before samples were equilibrated for 12 hours in a room temperature bath and shaken for 10 minutes to achieve solubility equilibrium (Wanninkhof et al, 1987).…”
Section: Gas Tracer Methods For Estimating Kmentioning
confidence: 99%
See 1 more Smart Citation
“…N 2 O and SF 6 were measured in 50 mL ground glass syringes via the headspace method (Ho et al, 2004). Approximately, 30 mL of ultra-high purity (UHP) nitrogen was added to each syringe before samples were equilibrated for 12 hours in a room temperature bath and shaken for 10 minutes to achieve solubility equilibrium (Wanninkhof et al, 1987).…”
Section: Gas Tracer Methods For Estimating Kmentioning
confidence: 99%
“…These processes include surf zone and riverine turbulence (Zappa et al, 2003), the convective oceanic mixed layer and rain on the water surface (Ho et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Enhancement in k w (660) is due mostly to increased near surface turbulence, whereas bubbles play a minor role (Ho et al 2000). Experiments in saltwater demonstrate that the relationship between rain and k w (660) is the same as in freshwater, but density stratification could inhibit vertical mixing and decrease the overall gas flux (Ho et al 2004;Zappa et al 2009). …”
Section: Rainmentioning
confidence: 97%
“…These studies began in the 1960s, where initial laboratory studies using O 2 invasion employed a rain simulators that had only 8-12 nozzles so only produced a few raindrops at a time, and only investigated a range of rain rates up to 17 mm h À1 (Department of Scientific and Industrial Research 1964;Banks and Herrera 1977;Banks et al 1984). In the last two decades, systematic laboratory studies examining the full range of rain rates encountered in nature have quantified the effect of rain on gas exchange (Ho et al 1997;Takagaki and Komori 2007), the interaction between rain and wind , the mechanism behind the enhancement (Ho et al 2000), the effect in saltwater Ho et al (2004); Zappa et al (2009). Furthermore, some modeling studies have been conducted to examine the potential effect of rain on air-sea CO 2 exchange Turk et al 2010).…”
Section: Rainmentioning
confidence: 99%
“…We have also not accounted for the effects of precipitation. Recently Ho et al (2004) demonstrated that short, intense rain events enhances gas exchange in the oceans. However, for much of the ocean for most of the time, such effects are expected to be smaller than those we highlight here.…”
Section: Discussionmentioning
confidence: 99%